Exploring Social Inclusion as a Factor for the Academic Achievement of Students Presenting with Special Educational Needs (SEN) in Schools: A Literature Review - Colum, Miriam; McIntyre, Karen (Irish Association of Teachers in Special Education, 2019)
This article presents a review of current research in social inclusion and how social inclusion may be a factor for the academic achievement of pupils with special educational needs (SEN). Attention is given to the placement of students with SEN in mainstream schools as an assumed social inclusive paradigm. Findings suggest that barriers to social inclusion exist in schools. Recommendations in terms of overcoming these barriers are presented.
Keywords: inclusion; social inclusion; special educational needs; Academic achievement; barriers to social inclusion